Various Pharmacological Activities in the Development of Kombucha as A Functional Food Ingredient with Economic Potential: A Literature Review - Rezaldi, Firman; Agustina, Nia; Wisnuwardhani, Paramita; Huda, Fahmi Alamil; Suminar, Erni (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
Kombucha is a fermented beverage produced by a symbiotic culture of bacteria and yeast (SCOBY) and has gained increasing attention as a functional food due to its bioactive compounds. This literature review aims to evaluate the pharmacological activities of kombucha and its potential development as a functional food with economic value. A systematic literature review was conducted using reputable international databases, including Scopus, Web of Science, PubMed, and ScienceDirect, covering publications from 2015 to 2025. The findings indicate that kombucha consistently exhibits antioxidant, antibacterial, anti-inflammatory, antidiabetic, anticancer, and cosmetic-related bioactivities. These effects are influenced by substrate type, fermentation conditions, and microbial composition, which determine the production of organic acids, polyphenols, flavonoids, and postbiotic metabolites. Beyond its health benefits, kombucha contributes significantly to economic development through product diversification, utilization of local resources and agro-industrial by-products, and entrepreneurial opportunities for small and medium enterprises. Nevertheless, challenges related to quality standardization, food safety, and health claim regulations remain critical issues. Overall, kombucha demonstrates strong potential as a functional food and an economically valuable fermented biotechnology product.